Parametric analysis on external dissipative link system for seismic protection of low rise R.C. buildings - Mario Lucio Puppio; Martina Ferrini (Fracture and Structural Integrity)
The seismic rehabilitation of existing R.C. and masonry buildings is a topical issue in Civil Engineering. A useful technique consists in the introduction of the external bracing system. This kind of intervention can be improved through the introduction of dissipative links, investigated here with the help of some examples. The links are made of common steel profiles: length, geometry and positioning are considered as design parameters. A general procedure of link-bracing optimization is proposed by applying a set of identical external restraints. The adopted dissipative links allow a cheaper and more effective design both in terms of ULS and of DLS: the damages are addressed in a small area allowing easy replacement of the links in case of an earthquake.